A Project Feasibility Study Child Care Training Center - Gaspar, Vincent Jonathan (College of Engineering, 1994)
Child care practices play a vital role in child growth and development. About a decade ago, the physical, psychological and social aspects of child growth were viewed as separate entities in the proper care of children. Nowadays, modern psychologists believe that these aspects must be integrated and properly enhanced in the child's stages of development. This project aims to provide its target customers with the proper concepts and tools in health care, safety, nutrition, social and behavioral guidance, and pre-school training through the establishment of Child Care Training Center. Child Care Training Center (CCTC) will act as a private educational institution that offers a training program to its target customers from the southern portion of Metro Manila. These customers have been selected as determined in the market study of this project. Upon its operations, the customers can proceed to CCTC's location in Makati, Metro Manila and avail of a training program that is aimed to be recognized by the Department of Education, Culture and Sports. The training center itself was specifically designed to offer consultancies and workshops and provide instructional materials from UNICEF, World Health Organization and the Department of Health in order to serve its training purposes. The initial operations of CCTC necessitate an investment of about P4.7 million. Financial requirements will be availed through stockholders and the Social Security System's Financial Plan for Vocational and Technical Schools. Throughout its operations, the project aims to have an ROI of 14%. CCTC has the ultimate goal to improve the overall conditions of a child's growth and development. It also aims to serve the society by generating income and employment and increase the child rearing abilities of its customers.